A low noise CMOS camera system for 2D resonant inelastic soft X-ray scattering - Andresen, Nord; Bakalis, Christos; Denes, Peter; Goldschmidt, Azriel; Johnson, Ian; Joseph, John M.; Karcher, Armin; Krieger, Amanda; Tindall, Craig (Frontiers in Physics, 2023)
Resonant Inelastic X-ray Scattering (RIXS) is a powerful spectroscopic technique to study quantum properties of materials in the bulk. A novel variant of RIXS, called 2D RIXS, enables concurrent measurement of the scattered X-ray spectrum for a wide range of input energies, improving on the typically low throughput of 1D RIXS. In the soft X-ray domain, 2D RIXS demands an X-ray camera system with small pixels, large area, high quantum efficiency and low noise to limit the false detection rate in long duration exposures. We designed and implemented a 7.5 Megapixel back-illuminated CMOS detector with 5 μm pixels and high quantum efficiency in the 200–1,000 eV X-ray energy range for the QERLIN 2D RIXS spectrometer at the Advanced Light Source. The QERLIN beamline and detector are currently in commissioning. The camera noise from in-situ 3 s long dark exposures is 7e− or less and the leakage current is 6.5 × 10−3 e−/(pixel ∙ s). For individual 500 eV X-rays, the expected efficiency is greater than 75% and the false detection rate is ∼1 × 10−5 per pixel.